BREASTFEEDING SELF-EFFICACY (BSE): COMPARATION BETWEEN ANTENATAL AND POSTPARTUM PERIOD - Ayut Merdikawati; Muladefi Choiriyah (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2019)
Breastfeeding is the process of giving mother’s breast milk to baby. Breast milk is the best nutrition for babies. However, there are inhibiting factors that influence mother to decide stop breastfeed. One of the factors is the low Breastfeeding Self-Efficacy (BSE). BSE can be used to predict mothers, who will stop the breastfeeding earlier in the future. BSE will increase during pregnancy until 6 weeks postpartum. The purpose of this study was to analysis comparation of BSE during third trimester pregnancy and postpartum period. The design of this study was observational analytic with a prospective cohort study approach. The study was conducted in Malang, on Kedungkandang District from January to May 2018. Fifty-eight respondents were involved in this study. The instruments used in this study were Prenatal Breastfeeding Self Efficacy Scale (PBSES) and Breastfeeding Self-Efficacy Scale Short Form (BSES-SF). The data were analysed using paired t-test. The result of this study was the average BSE score of mothers during pregnancy is 57,59 ± 7,49 and BSE at postpartum, 58.53 ± 5,99. While, the paired t-test obtained a p value of 0.365, it can be concluded that there were no significant differences between BSE mothers during pregnancy and postpartum.